Serial Dopamine Transporter Imaging of Nigrostriatal Function in Parkinson’s Disease With Probable REM Sleep Behavior Disorder - Cao, Ruihua; Chen, Xingui; Xie, Chengjuan; Hu, Panpan; Wang, Kai (Frontiers in Neuroscience, 2020)
The current study aimed to confirm whether probable rapid eye movement sleep behavior disorder (pRBD) is associated with a specific pattern of striatal dopamine depletion in an international, multicenter, prospective cohort of patients with Parkinson’s disease (PD). Two hundred and seventy de novo, drug-naïve patients with PD underwent dopamine transporter (DAT) single photon emission computed tomography with 123I-FP-CIT at baseline and 1, 2, and 4 years after the initial scan. The diagnosis of pRBD was based on the 10-item RBD Screening Questionnaire. Striatal DAT binding levels and their rates of decline were compared between patients with pRBD and those without. At baseline, patients in the PD-pRBD+ group showed lower striatal DAT binding in the caudate (which was more pronounced in the less affected hemisphere) and in the putamen. During the 4-year follow-up, patients in the PD-pRBD+ group consistently exhibited greater DAT loss than patients in the PD-pRBD- group with comparable disease duration in all four striatal subregions. These patients also exhibited a more rapid decrease in DAT binding in the caudate and a less prominent interhemispheric asymmetry in the putamen. The distinct pattern of striatal DAT depletion may contribute to a more malignant phenotype of PD associated with RBD, specifically faster progression of motor symptoms.